Impact of Leverage, Activity Ratio, Market Value, and Bond Rating - Dewi Cahyani Pangestuti; Marlina; Siti Hidayati (Jurnal Manajemen dan Organisasi, 2022)
This research is a quantitative investigation of the impact of leverage, activity ratio, and market value on PEFINDO's bond ratings for the years 2018 to 2021. This study's sample employed the strategy of purposive sampling to acquire as many as 25 financial institutions. Using a significance threshold of 0.05, Eviews version 12.0 was used to test hypotheses using regression analysis of panel data. The results of testing variable activity ratios with the Total Assets Turnover (TAT) proxy and market value with the Market to Book Value (MBV) proxy indicated a significant negative influence on the bond ratings of financial companies, whereas leverage with a Debt to Assets Ratio (DAR) proxy indicates no significant influence. The advice that may be offered to a firm, specifically the results of this study, can be utilized as material for projecting bond ratings in order to make proper judgments regarding bond issuance and is anticipated to be material for company evaluation and performance improvement. And the results of this study can help investors predict bond ratings by giving them information and insights. This lets them make investment decisions and choose the type of company to invest in to make the most money and reduce risk.